MAJELIS AZZAHIR SEBAGAI WUJUD UPAYA UMAT MUSLIM DALAM MEREDUKSI RADIKALISME ISLAM DI INDONESIA - Furkon, Furkon (IAIN Purwokerto, 2020)
After the reforms, there have been many changes in the social and religious structure in Indonesia, namely the emergence of Islamic extremism and radicalism. The explosion of terrorism in the name of Islam that occurred between 1998 and 2019 brought the face of Indonesian Islam to the spotlight in the world. In fact, the true Islam in Indonesia is Islam which emphasizes moderate principles (tawassuth / washatiah). Likewise, the Azzahir Assembly is one of the da'wah media containing blessings and da'wah as well as one of the assemblies that emphasizes the values of Islam rahmatan lil 'alamin. This Islamic characteristic becomes a stronghold of preventing radical religious ideology. The purpose of this study is to find out how the Azzahir Assembly can reduce Islamic radicalism in Indonesia. This study uses an epistemological-historical- holistic approach to explore the concept of Islamic moderation in the context of the Indonesian nation and the shallowness of religious reasoning. The subjects of this research are books, social media, news media or other sources that can be used as a reference. The object of this research is the Azzahir Assembly. Data collection techniques used were observation, collection of literature both books or online literature, and interviews. Data processing techniques used are data reduction, display, and verification then analyzed using qualitative descriptive analysis. The results of this study are the Assembly of Azzahir as the Sholawat Council can be one of the media or tools in reducing Islamic radicalism in Indonesia.